(untitled) (ModaPalavra e-periódico, 2017)
This is an interview with Prof. Ana Paula Celso de Miranda on the launch of the second edition of the book “Fashion Consumption: a Person-Object Relationship”. The author talks about her motivation for this work and her 20 years of academic trajectory in the field of fashion. The news this edition brings are flagged by Ana Paula in the interview. In addition to the partnership with the stylist Ronaldo Fraga, in this edition the author counts with the contribution of Prof. Olga Pepece and Profº Eduardo Maciel. The author indicates who is meant to read her book, points out some paths in fashion research and talks about the work she has been developing.